Cases and stories of transformative action research : five decades of collaborative action and learning - Bilorusky, John A. (John Alan) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Transformative Inquiry Through Action Research in Practice draws on author John Bilorusky's liftetime experiences of conducting action research in real-world settings. The two volumes (this book and A Half Century of Living and Doing Transformative Inquiry Through Action Research) comprehensively lay out the principles of and examine case studies in action research. This volume examines a number of case studies and application for action research, detailing research plans and hypotheses, and what actually happens on real research projects - both things that work well and the challenges of working in a real world environment. In showcasing action research in educational, health, governmental and other settings, this book will be suitable for students coming to action research for the first time and for researchers wanting to widen their knowledge and experience of this method in practice"--
OCLC-licensed vendor bibliographic record.
Keywords: Action research -- Case studies; Evaluation research (Social action programs) -- Case studies; PSYCHOLOGY / Research & Methodology; SOCIAL SCIENCE / Research